The Enforcement Judge’s Authority over International Sports Arbitration Awards: A Comparative Study between the Saudi Legal Framework and Swiss Law - Nardeen Abdulmohsen Mohammed Eraqi; Al-Hanouf Abdulaziz Al-Salmi (International Journal of Law Research and Studies, 2025)
This study explores the authority vested in the enforcement judge concerning arbitral awards issued by the Court of Arbitration for Sport (CAS), within the context of both the Saudi legal framework and Swiss law. The objective is to examine the legal structures governing the enforcement of such awards in each jurisdiction. The research employs a comparative analytical methodology by examining the relevant statutory provisions in both systems. It discusses the legal nature of international sports arbitration awards, the legal basis for their recognition, and proceeds to assess the scope of judicial authority in enforcing such awards. This includes analyzing the statutory requirements for enforcement and the extent of judicial discretion granted under each legal regime. The key finding of the study is that the legal characterization of CAS awards is a determinative factor in defining the scope of judicial oversight during the enforcement phase. In the Saudi legal system, the enforcement judge exercises broad and stringent authority to verify compliance with all procedural and substantive requirements prior to execution and is obligated to refuse enforcement in case of any deficiency. Conversely, under Swiss law, enforcement authorities operate under more constrained powers, as CAS awards are treated in line with domestic judgments, pursuant to the Swiss Federal Act on Private International Law. The study recommends amending Article 11(1) of the Saudi Enforcement Law by replacing the term “courts of the Kingdom” with “dispute resolution bodies in the Kingdom,” as jurisdiction may, in practice, be held by entities other than traditional courts such as judicial committees, arbitration centers, or administrative tribunals thus promoting legislative clarity and alignment with the actual structure of dispute resolution mechanisms in the Kingdom.